Scrutinizes the Sustainable Role of Halophilic Microbial Strains on Oxygen-Evolving Complex, Specific Energy Fluxes, Energy Flow and Nitrogen Assimilation of Sunflower Cultivars in a Suboptimal Environment - Ali, Fiza; Wei, Xiangying; Siddiqui, Zamin Shaheed; Chen, Jianjun; Ansari, Hafiza Hamna; Wajid, Danish; Shams, Zafar Iqbal; Abbasi, Muhammad Waseem; Zafar, Urooj (Frontiers in Plant Science, 2022)
Environmental extremes such as hypersaline conditions are major threats to agricultural productivity therefore halophilic microbes are quite a vogue to impart salt tolerance in plants. Hence the sustainable impact of halophilic microbial strains on oxygen-evolving complex (OEC), energy compartmentalization, harvesting efficiencies (LHE), specific energy fluxes (SEF), and nitrogen assimilation of oilseed crops (Sunflower cultivars) in a suboptimal environment were tested. Plants were grown in a plastic pot (15 × 18 cm2) containing sterilized (autoclaved at 120 ºC for one hour) soil. Twenty-five ml suspension (107 CFU/ml) of each respective Bacillus species i.e., Bacillus cereus strain KUB-15 and KUB-27 (accession number NR 074540.1) and Bacillus licheniformis strain AAB9 (accession number MW362506), were applied via the drenching method. Month-old plants were subjected to salt stress via the gradual increment method. The energy compartmentalization of microbial inoculated plants exposed to salt stress revealed higher activity of photosystem II (PSII) at the donor side, lesser photo-inhibition, and increased performance of oxygen evolving complex as compared to control. High potassium (K+) and low sodium (Na+) ions in treated leaves with the activated barricade of antioxidant system stimulated by Bacillus strains favored the enhanced photochemical efficiency, smooth electron transport, lesser energy dissipation in the stressed plants. Moreover, the results reveal the increased activity of Nitrite reductase (NiR) and nitrate reductase (NR) by microbial inoculation which elevated the nitrogen availability to the salt-stressed plant. The current research concludes that the application of bio-inoculants already inhabiting the hyper-saline environment offers the great potential to enhance salt tolerance in sunflowers by modulating their water uptake, chlorophyll, nitrogen metabolism and better photochemical yield.